2000
DOI: 10.1080/03079450020016878
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between egg size and subgroup J avian leukosis virus in eggs from broiler breeders

Abstract: Hatching eggs from three broiler breeder flocks that had experienced losses from myeloid leukosis were tested for infection with avian leukosis virus of subgroup J (ALV-J). Sufficient eggs were positive in two flocks to relate infection to egg weight. Allantoic fluid, embryonic tissue and yolk were collected after 18 days of incubation. The albumen and allantoic fluid were tested by enzyme-linked immunosorbent assay (ELISA) for group-specific (gs) antigen and all specimens were inoculated onto cell cultures to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Body weight suppression has also been shown in leghorns infected with several ALV subgroups (A, B, C, D and F), subgroup C being most severe in this regard (Carter & Smith, 1984). Spencer et al (2000) have shown that lighter eggs (<60 g) from subgroup J-positive broiler breeder flocks with myeloid leukosis tested more frequently positive for group-specific antigen and virus.…”
Section: Introductionmentioning
confidence: 97%
“…Body weight suppression has also been shown in leghorns infected with several ALV subgroups (A, B, C, D and F), subgroup C being most severe in this regard (Carter & Smith, 1984). Spencer et al (2000) have shown that lighter eggs (<60 g) from subgroup J-positive broiler breeder flocks with myeloid leukosis tested more frequently positive for group-specific antigen and virus.…”
Section: Introductionmentioning
confidence: 97%
“…In the field, the presence of ALV-J infection is associated with variable tumor types, including myelocytoma, renal tumors, hemangioma, and others (9, 29, 29a, 30). The high incidence of tumors decreases production, and virus eradication increases production costs (7,22,28). Simple, rapid, and sensitive diagnostic methods for detection of ALV-J need to be developed to address the need for the rapid diagnosis (16,17,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…That number may well increase; the J subgroup was only discovered in 1989, causing myelocytic myeloid leukosis in meat-type chickens (Payne et al 1991a,b;Bai et al, 1995;Payne, 1998). Since its discovery, in the UK, it has been detected elsewhere (Fadly & Smith, 1999;Spencer et al, 2000). Although ALV-J has been largely associated with myelocytic myeloid leukosis in meat-type chickens, it has recently been identified as being associated with another neoplasm, erythroblastosi s (Venugopal et al, 2000b), the identity of the subgroup being made by subgroup-specific PCR.…”
Section: Avian Leukosis Virusesmentioning
confidence: 99%
“…Although ALV-J has been largely associated with myelocytic myeloid leukosis in meat-type chickens, it has recently been identified as being associated with another neoplasm, erythroblastosi s (Venugopal et al, 2000b), the identity of the subgroup being made by subgroup-specific PCR. The latter was also used by Spencer et al (2000) in an investigation of observations in the field that broiler breeders infected with subgroup J virus produced increased numbers of smaller eggs.…”
Section: Avian Leukosis Virusesmentioning
confidence: 99%
See 1 more Smart Citation